The Theory of Dyadic Morality: Reinventing Moral Judgment by Redefining Harm. (February 2018) - Schein, Chelsea; Gray, Kurt
The nature of harm—and therefore moral judgment—may be misunderstood. Rather than an objective matter of reason, we argue that harm should be redefined as an intuitively perceived continuum. This redefinition provides a new understanding of moral content and mechanism—the constructionist Theory of Dyadic Morality (TDM). TDM suggests that acts are condemned proportional to three elements: norm violations, negative affect, and—importantly—perceived harm. This harm is dyadic, involving an intentional agent causing damage to a vulnerable patient (A→P). TDM predicts causal links both from harm to immorality (dyadic comparison) and from immorality to harm (dyadic completion). Together, these two processes make the "dyadic loop, " explaining moral acquisition and polarization. TDM argues against intuitive harmless wrongs and modular "foundations, " but embraces moral pluralism through varieties of values and the flexibility of perceived harm. Dyadic morality impacts understandings of moral character, moral emotion, and political/cultural differences, and provides research guidelines for moral psychology.